STEM: Project based learning to enhance conceptual understanding of two-dimensional shapes and and develop the pancasila student profile - Ukhti Raudhatul Jannah; Ainur Rofiq Hafsi; Sri Indriati Hasanah; Hasan Basri; Septia Nurhidayati; Akhmad Riski Rifanda; Sisca Patricia Dwi Agustin (Premiere Educandum : Jurnal Pendidikan Dasar dan Pembelajaran, 2024)
This study aims to explore the conceptual understanding of shapes through the integration of STEM with Project-Based Learning (PjBL) in enhancing elementary students' understanding of two-dimensional shapes and developing the Pancasila Student Profile. The research approach of this study is qualitative. Data collection techniques employed in this study include interviews, observations, and analysis of student work. The subjects of this research are three second-grade students who face difficulties in understanding the concepts of two-dimensional geometry. The research findings indicate that the STEM-integrated PjBL approach can The research findings describe that after the STEM integrated PjBL approach students can fulfill 4-7 indicators of concept understanding, namely presenting concepts in various mathematical representations, developing necessary and sufficient conditions for a concept, using, exploiting and selecting certain operations and applying concepts to problem solving Additionally, PjBL-STEM fosters character development pancasila student profile such as collaboration, critical thinking, and creativity.